(untitled) (Scientia Agricola, 2012)
Plants have shown different responses to fertilization with rock phosphate, including responses through alteration of the attributes of rhizospheric soil. The objective of this study was to evaluate soil pH alterations and alterations in the contents of forms of phosphorus in the rhizosphere of soil fertilized with rock phosphate as a result of cultivation of species of plants. An experiment was developed under greenhouse conditions to evaluate alterations in the pH and in the forms of phosphorus in the rhizosphere of an Oxisol fertilized with rock phosphate and cultivated with four species. Treatments consisted of the cultivation of four species of soybean - Glycine max (L.) Merrill, brachiaria grass - Brachiaria brizantha Hochst Stapf, millet - Pennisetum glaucum (L.) R. Brown, and sorghum - Sorghum bicolor (L.) Moench grown in PVC columns filled with soil and divided with a nylon screen (25 µm mesh) to impede root growth in part of the column. After 45 days of cultivation, the soil was divided into the layers of 0-1, 1-2, 2-3, 3-4, 4-5, 5-7, 7-9, and 9-14 mm from the rhizoplane and air dried to determine pH and P contents through Hedley fractionation. In the 1-2 and 2-3 mm layers, soybean cultivation caused an increase in pH when compared to the control treatment (without plants). In the other layers, there were no alterations in pH due to cultivation of plants. The cultivation of millet, brachiaria grass, and sorghum reduced the inorganic P content in the most labile forms only in the 0-1 mm layer from the rhizoplane.